Blending Cultural Heritage with Digital Design : A New Era in Pottery Motifs and Art - Yuniana Cahyaningrum; Sekar Kinanthi; A’imatul Magfiroh; Dani Eka Ramdhani (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2024)
The fusion of cultural heritage and digital technology has opened up new opportunities in the art of motifs and pottery making. This article explores design innovations that utilize digital technology to recreate traditional motifs in ceramic crafts. The research examines how techniques such as parametric design, 3D printing, and virtual reality can be used to preserve, adapt, and introduce cultural motifs to a wider audience. Case studies from several traditional artisan communities are analyzed to understand the impact of technology on the creative process, production efficiency, and preservation of cultural values. The results show that the integration of digital technology not only increases design flexibility but also strengthens the connection between tradition and modern innovation. This article provides important insights into the role of digital technology in fostering the sustainability of traditional crafts, while motivating future cross-disciplinary collaborations.